2003
DOI: 10.1046/j.1365-2133.2003.05223.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma, squamous cell carcinoma and melanoma of the skin: analysis of the Singapore Cancer Registry data 1968-97

Abstract: The incidence rates of skin cancer increased in Singapore during the period 1968-97. Fairer-skinned Chinese had a higher incidence of skin cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
4
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(124 citation statements)
references
References 26 publications
8
111
4
1
Order By: Relevance
“…As for the nonmelanoma type, Caucasians have the highest incidence compared with Asian and Hispanic races. However, it rarely occurs in black populations [5][6][7]. Monitoring the incidence of skin cancer has shown that there is an increasing trend in most countries in the world.…”
Section: Introductionmentioning
confidence: 99%
“…As for the nonmelanoma type, Caucasians have the highest incidence compared with Asian and Hispanic races. However, it rarely occurs in black populations [5][6][7]. Monitoring the incidence of skin cancer has shown that there is an increasing trend in most countries in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in its early detection and treatment, melanoma incidence has substantially increased worldwide in recent decades [1,2,3]. In Caucasian populations, the incidence has increased by 3-7% per year [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous squamous cell carcinoma (cSCC) is a common skin cancer with an incidence rate of 12–29/100,000/year in Europe and 700/100,000/year in Australia [1,2,3,4,5,6,7]. Populations with fair skin that experience high cumulative UV exposure are at highest risk for cSCC development, sun-exposed areas being majorly affected [8,9,10].…”
Section: Introductionmentioning
confidence: 99%